Zachowania przedsiębiorców w momentach krytycznych jako czynnik wpływający na rozwój - Gudkova, Svetlana; Glinka, Beata (Entrepreneurs' Behaviour in Critical Incidents as a Factor Influencing Development, 2006)
The aim of this article is to present selected factors influencing small enterprises development. The analysis is based on research conducted among small enterprises. The special emphasis is put on the way critical incidents influence the processes of development. The authors analyse types of entrepreneurs' reactions to the critical situations considered also as a source of innovation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 267-273